Fiber-reinforced resin and method for manufacturing the same
Patent Information
- Application Number
- JP2023046578
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-03-23
AI Technical Summary
【0009】 本発明によれば、曲げ物性を高められた成形体が得られるUDシートまたはその成形体である繊維強化樹脂、およびその製造方法が提供される。
Smart Images

Figure 0007943836000001 
Figure 0007943836000002 
Figure 0007943836000003
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a fiber-reinforced resin and a production method thereof. BACKGROUND ART
[0002] A thin-film fiber-reinforced resin (hereinafter also simply referred to as "Uni-Direction (UD) sheet") that includes a plurality of reinforcing fibers oriented and arranged in one direction, and a resin composition (matrix resin) impregnated into the reinforcing fibers is known. This UD sheet is used as various reinforcing materials due to its high strength.
[0003] Patent Document 1 describes a UD sheet in which the crystallinity of the resin portion exceeds 50% by using a polypropylene-based resin, a phenol-based antioxidant and a phosphorus-based antioxidant as essential components of the resin portion, and by adding a crystal nucleating agent or by a method of heating to a temperature higher than the glass transition temperature of the polypropylene-based resin followed by cooling. Patent Document 1 states that this UD sheet provided a fused body obtained by laminating, heating and pressurizing that had good thermal stability and bending properties. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0004] PATENT DOCUMENT 1 Japanese Unexamined Patent Publication No. 2017-43672 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0005] As also described in Patent Document 1, various methods for enhancing the bending properties of molded bodies of UD sheets have been studied. However, according to the findings of the present inventors, molded bodies obtained from the UD sheet described in Patent Document 1 sometimes fail to satisfy the bending properties required for various applications.
[0006] The present invention has been made in view of the problems of the prior art described above, and aims to provide a UD sheet or a fiber-reinforced resin which is a molded article with improved bendability, and a method for manufacturing the same. [Means for solving the problem]
[0007] One embodiment of the present invention for solving the above problems relates to the fiber-reinforced resins described below [1] to [7]. [1] comprising a plurality of reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin, The matrix resin has a long period of crystals at 23°C of 200 Å or more, as determined by small-angle X-ray scattering. Fiber-reinforced resin. [2] The matrix resin has a degree of crystallinity of 45% or more at 80°C. [1] Fiber-reinforced resin as described above. [3] The matrix resin includes polypropylene, The fiber-reinforced resin described in [1] or [2]. [4] The polypropylene has a melting point of 163°C or lower. [3] Fiber-reinforced resin as described above. [5] The polypropylene has a melt flow rate (MFR) of 100 mm / 10 min or more, measured at 230°C and a 2.16 kg load in accordance with ASTM D1238. Fiber-reinforced resin as described in [3] or [4]. [6] The reinforcing fibers include carbon fibers, A fiber-reinforced resin as described in any of [1] to [5]. [7] The fiber volume fraction (Vf) is between 20% and 60%. A fiber-reinforced resin as described in any of [1] to [6].
[0008] Another embodiment of the present invention for solving the above problems relates to a method for producing fiber-reinforced resin as described below [8]. [8] A step of preparing a composite material comprising a plurality of reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin, The composite material is annealed at an annealing temperature within the following range, where Tm is the melting point of the matrix resin. Tm -20℃ < Annealing temperature < Tm A method for producing fiber-reinforced resin having the following characteristics. [Effects of the Invention]
[0009] According to the present invention, a UD sheet or a fiber-reinforced resin which is a molded article with enhanced bending properties is provided, as well as a method for producing the same. [Modes for carrying out the invention]
[0010] [Fiber-reinforced resin] One embodiment of the present invention relates to a fiber-reinforced resin comprising a plurality of reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin.
[0011] This fiber-reinforced resin may be a single layer of UD sheet, or a laminate formed by laminating and fusing multiple UD sheets together. It may also be a molded article formed by processing a UD sheet or its laminate into a predetermined shape or fusing it to another component.
[0012] This fiber-reinforced resin has a matrix resin crystal long period of 200 Å or more at 23°C, as determined by small-angle X-ray scattering. In other words, the lamellar thickness of the matrix resin crystals is thicker than in conventional materials. This efficiently enhances the bending properties due to the matrix resin crystals.
[0013] When increasing the crystallinity of the matrix resin, by delaying the crystallization rate, each crystal (lamella) can be sufficiently grown, and the lamella thickness can be made sufficiently large. For example, when attempting to increase the crystallinity of a thermoplastic resin by annealing (heat treatment), annealing is usually performed at a temperature near the midpoint between the glass transition temperature (Tg) where the crystallization acceleration is the highest and the melting point (Tm). In contrast, by performing annealing at a temperature closer to (higher than) Tm than the aforementioned midpoint region and intentionally delaying crystallization, the lamella thickness can be made sufficiently large to enhance the bending properties of the fiber-reinforced resin. It should be noted that increasing the annealing temperature can also improve the bending properties of the fiber-reinforced resin at high temperatures. Alternatively, crystallization may be delayed more than usual by using a nucleating agent with a slow crystallization rate, or by not using a nucleating agent.
[0014] From the above viewpoint, the long period of the crystal of the matrix resin at 23°C is preferably 200 Å or more and 500 Å or less, more preferably 200 Å or more and 450 Å or less, and even more preferably 250 Å or more and 400 Å or less. Further, from the viewpoint of improving the bending properties of the fiber-reinforced resin at high temperatures, the long period of the crystal of the matrix resin at 80°C is preferably 200 Å or more and 500 Å or less, more preferably 200 Å or more and 450 Å or less, and even more preferably 250 Å or more and 400 Å or less.
[0015] The crystallinity of the matrix resin at 23°C is preferably 48% or more, preferably 48% or more and 70% or less, and more preferably 50% or more and 60% or less. Further, from the viewpoint of improving the bending properties of the fiber-reinforced resin at high temperatures, the crystallinity of the matrix resin at 80°C is preferably 45% or more, preferably 45% or more and 70% or less, and more preferably 48% or more and 60% or less.
[0016] The long period of the crystal is the period of the structure combining the crystal part (lamella part) and the amorphous part in the matrix resin. In addition, the aforementioned crystallinity refers to the ordinary crystallinity of the matrix resin (for example, the ratio of α-crystals in the case of polypropylene).
[0017] The long period of crystals is measured by the small-angle X-ray scattering method (SAXS) using CuKα radiation. The crystallinity is measured by the wide-angle X-ray diffraction method (WAXD) using CuKα radiation.
[0018] The material of the matrix resin is not particularly limited as long as it is a crystalline thermoplastic resin.
[0019] Examples of the above thermoplastic resins include polyolefin resins containing polyethylene, polypropylene, polybutene, poly-4-methyl-1-pentene and the like, polyamide resins, polyester resins, polystyrene resins, thermoplastic polyimide resins, polyamideimide resins, polycarbonate resins, polyphenylene ether resins, polyphenylene sulfide resins, polyacetal resins, acrylic resins, polyetherimide resins, polysulfone resins, polyether ketone resins, polyether ether ketone resins, polyarylate resins, polyether nitrile resins, vinyl chloride resins, ABS resins, and fluororesins. The above polyolefins may be copolymers including ethylene / propylene copolymers, ethylene / 1-butene copolymers, ethylene / propylene / diene copolymers, ethylene / carbon monoxide / diene copolymers, ethylene / ethyl (meth)acrylate copolymers, ethylene / glycidyl (meth)acrylate, and ethylene / vinyl acetate / glycidyl (meth)acrylate copolymers. These thermoplastic resins may be derived from fossil fuels, may be derived from biomass raw materials, or may be a mixture thereof.
[0020] Among these, polyamide resins and polyolefin resins are preferable from the viewpoint of further improving the moldability of the fiber-reinforced resin, polyolefin resins are more preferable because they easily increase the lamella thickness to enhance the flexural strength of the molded article, and polypropylene is even more preferable because it has good heat resistance, chemical resistance and water resistance.
[0021] The matrix resin may be a resin composition containing additives. Examples of the above additives include known fillers (inorganic fillers, organic fillers), pigments, dyes, nucleating agents, weather stabilizers, heat stabilizers, antistatic agents, anti-slip agents, antioxidants, antifungal agents, antibacterial agents, flame retardants, and softeners. For example, when UD sheets are fused by laser irradiation during the manufacture of a molded article, the matrix resin is preferably a resin composition containing a dye that absorbs laser light of the irradiated wavelength. The above dye may be any dye that absorbs light of any wavelength between 300 nm and 3000 nm, and carbon black is preferred.
[0022] Furthermore, the matrix resin may also contain other resins or other components, such as short fibers shorter in length than the reinforcing fibers arranged in a unidirectional orientation.
[0023] When the matrix resin is polypropylene, it is preferable that the polypropylene has a melting point greater than 150°C and 165°C or less. The higher the melting point of polypropylene, the easier it is to form a sufficiently large amount of crystalline components and improve the flexibility of the molded article. The melting point of polypropylene is usually 165°C or less. Furthermore, according to the inventors' findings, using polypropylene with a melting point lower than 165°C makes it easier to increase the lamellar thickness (increase the long period) and improve the flexibility of the molded article. From the above viewpoint, it is preferable that the polypropylene has a melting point of 163°C or less, more preferably greater than 150°C and 163°C or less, even more preferably between 155°C and 163°C, and particularly preferably between 160°C and 163°C. The melting point of polypropylene is a value measured by the DSC method. Furthermore, when the matrix resin contains multiple types of polypropylene, the melting point of the matrix resin is the temperature indicated by the largest peak shown by the mixture of these multiple types of polypropylene.
[0024] The type of polypropylene is not particularly limited and may be a propylene homopolymer, a propylene copolymer, or a mixture thereof. The stereoregularity of the polypropylene is also not particularly limited and may be isotactic, syndiotactic, or atactic. The stereoregularity is preferably isotactic or syndiotactic.
[0025] The polypropylene may be unmodified polypropylene (P1), modified polypropylene (P2) containing carboxylates or the like bonded to the polymer chain, or a mixture thereof, but a mixture thereof is preferred. In the above mixture, the mass ratio of unmodified polypropylene (P1) to the total mass of unmodified polypropylene (P1) and modified polypropylene (P2) [(P1) / (P1+P2)] is preferably 80% by mass or more and 99% by mass or less, more preferably 85% by mass or more and 98% by mass or less, and even more preferably 90% by mass or more and 97% by mass or less.
[0026] The above-mentioned unmodified polypropylene (P1) preferably has a melt flow rate (MFR) of 50 g / 10 min or more, measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238, more preferably 100 g / 10 min to 500 g / 10 min, and even more preferably 130 g / 10 min to 500 g / 10 min. When the MFR is within this range, the resin 144 is easily impregnated into the reinforcing fiber 200.
[0027] The above-mentioned unmodified polypropylene (P1) preferably has a weight-average molecular weight (Mw) of 50,000 to 300,000, and more preferably 50,000 to 200,000.
[0028] The above-mentioned unmodified polypropylene (P1) is a resin component mainly composed of propylene-derived structural units, with a propylene-derived structural unit content of 50 mol% or more. In addition to propylene-derived structural units, the above-mentioned unmodified polypropylene (P1) may also contain structural units derived from α-olefins other than propylene, conjugated or unconjugated dienes, or polyenes.
[0029] When the above-mentioned unmodified polypropylene (P1) is a copolymer, examples of α-olefins as copolymer components include ethylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 1-nonene, 1-octene, 1-heptene, 1-hexene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, which are α-olefins (including propylene) having 2 to 20 carbon atoms. Of these, 1-butene, ethylene, 4-methyl-1-pentene, and 1-hexene are preferred, and 1-butene and 4-methyl-1-pentene are more preferred. Examples of conjugated and unconjugated dienes as copolymerization components include butadiene, ethylidene norbornene, dicyclopentadiene, and 1,5-hexadiene. Two or more of these α-olefins, conjugated dienes, and unconjugated dienes may be used in combination.
[0030] The above-mentioned modified polypropylene (P2) is polypropylene containing carboxylates, etc., bonded to the polymer chain. In particular, the presence of modified polypropylene (P2) carboxylates tends to increase the interfacial adhesion strength between the reinforcing fiber 200 and the resin 144.
[0031] The weight-average molecular weight (Mw) of the above-mentioned modified polypropylene (P2) is preferably 1,000 or more and 100,000 or less, and more preferably 2,000 or more and 80,000 or less.
[0032] Modified polypropylene (P2) can be synthesized by known methods such as radical graft polymerization of an unmodified propylene polymer and a monomer having a carboxylic acid structure.
[0033] The above-mentioned unmodified propylene polymer may be any propylene polymer similar to the unmodified polypropylene (P1) described above, but it is preferable that it be a propylene homopolymer, or a copolymer of propylene and α-olefin such as ethylene-propylene copolymer, propylene-1-butene copolymer, and ethylene-propylene-1-butene copolymer.
[0034] The monomer having the above carboxylic acid structure may be a monomer having a carboxylic acid group or a monomer having a carboxylic acid ester. The carboxylic acid group may be neutralized, and the carboxylic acid ester may be saponified. Specific examples of these include ethylene-based unsaturated carboxylic acids, their anhydrides or esters, and compounds having an unsaturated vinyl group other than olefins.
[0035] Examples of ethylene-based unsaturated carboxylic acids include (meth)acrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, and isocrotonic acid. Examples of anhydrides include nadic acid (endosis-bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic acid), maleic anhydride, and citraconic anhydride.
[0036] Examples of compounds having unsaturated vinyl groups other than the olefins mentioned above include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate. (Meth)acrylic acid, including methacrylate, octadecyl (meth)acrylate, stearyl (meth)acrylate, tridecyl (meth)acrylate, lauroyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, isobolonyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. Esters, hydroxyl group-containing vinyls including hydroxyethyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl acrylate, lactone-modified hydroxyethyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl acrylate, epoxy group-containing vinyls including glycidyl (meth)acrylate and methylglycidyl (meth)acrylate, isocyanate group-containing vinyls including vinyl isocyanates and isopropenyl isocyanates, aromatic vinyls including styrene, α-methylstyrene, vinyltoluene, and t-butylstyrene, amides including acrylamide, methacrylamide, N-methylolmethacrylamide, N-methylolacrylamide, diacetone acrylamide, and maleic acid amide, vinyl esters including vinyl acetate and vinyl propionate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,This includes aminoalkyl (meth)acrylates such as N-dimethylaminopropyl (meth)acrylate, N,N-dipropylaminoethyl (meth)acrylate, N,N-dibutylaminoethyl (meth)acrylate, and N,N-dihydroxyethylaminoethyl (meth)acrylate; unsaturated sulfonic acids such as styrene sulfonic acid, sodium styrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid; and unsaturated phosphoric acids such as mono(2-methacryloyloxyethyl) acid phosphate and mono(2-acryloyloxyethyl) acid phosphate. Two or more of these may be used.
[0037] Of these, anhydrous ethylene-based unsaturated carbones are preferred, and maleic anhydride is more preferred.
[0038] Modified polypropylene (P2) can be synthesized by known methods. For example, the unmodified propylene polymer and the monomer having the carboxylic acid structure may be reacted in an organic solvent in the presence of a polymerization initiator, and then the solvent may be removed. Alternatively, the unmodified propylene polymer may be heated and melted, and the resulting molten product may be reacted with the carboxylic acid having an unsaturated vinyl group while stirring in the presence of a polymerization initiator. A mixture of the unmodified propylene polymer, the carboxylic acid having an unsaturated vinyl group, and a polymerization initiator may be supplied to an extruder and reacted while heating and kneading, and then a carboxylate salt may be obtained by neutralization or saponification.
[0039] Examples of polymerization initiators include various peroxide compounds such as benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)hexine-3, and 1,4-bis(tert-butylperoxyisopropyl)benzene, as well as azo compounds such as azobisisobutyronitrile. Two or more of these polymerization initiators may be used in combination.
[0040] Examples of the above organic solvents include aromatic hydrocarbons such as xylene, toluene, and ethylbenzene; aliphatic hydrocarbons such as hexane, heptane, octane, decane, isooctane, and isodecane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, and ethylcyclohexane; ester solvents such as ethyl acetate, n-butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and 3-methoxybutyl acetate; and ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone. Of these, the above organic solvents are preferably aromatic hydrocarbons, aliphatic hydrocarbons, and alicyclic hydrocarbons, and more preferably aliphatic hydrocarbons and alicyclic hydrocarbons. Two or more of these organic solvents may be used in mixture form.
[0041] In this case, from the viewpoint of treating the raw material for modified polypropylene (P2) as an aqueous dispersion, it is preferable that the monomer having the above-mentioned carboxylic acid structure is neutralized or saponified.
[0042] The above neutralization or saponification may be carried out by known methods using basic substances such as alkali metals or alkaline earth metals including sodium, potassium, lithium, calcium, magnesium, and zinc, other metals, inorganic amines including hydroxylamine and ammonium hydroxide, organic amines including ammonia, (tri)methylamine, (tri)ethanolamine, (tri)ethylamine, dimethylethanolamine, and morpholine, oxides, hydroxides, or hydrides of alkali metals or alkaline earth metals such as zinc, oxides, hydroxides, or hydrides of other metals, weak salts of alkali metals or alkaline earth metals including sodium carbonate, and weak salts of other metals.
[0043] The degree of neutralization or saponification achieved by these neutralization or saponification methods is preferably 50% to 100%, more preferably 70% to 100%, and even more preferably 85% to 100%, from the viewpoint of improving both the stability of the aqueous dispersion and the adhesion to the reinforcing fiber 200. It is preferable that all carboxylic acid groups in the modified polypropylene (P2) are neutralized or saponified, but some carboxylic acid groups may remain unneutralized or saponified.
[0044] Furthermore, the salt components of carboxylic acid groups can be detected and measured in quantity by methods such as detecting the metal species forming the salt using ICP emission spectrometry, and identifying the structure of the acid group salt using IR, NMR, mass spectrometry, or elemental analysis.
[0045] The matrix resin preferably has a melt flow rate (MFR) of 50 g / 10 min or more, measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238, more preferably 100 g / 10 min to 500 g / 10 min, and even more preferably 130 g / 10 min to 500 g / 10 min. When the MFR is within this range, it is easier to slow down the cooling rate and delay the crystallization rate, making it easier to increase the lamellar thickness and improve the degree of crystallinity.
[0046] The type of reinforcing fiber is not particularly limited, and carbon fiber, glass fiber, aramid fiber, alumina fiber, silicon carbide fiber, boron fiber, and metal fiber can be used as the reinforcing fiber. Of these, carbon fiber and glass fiber are preferred, and carbon fiber is more preferred.
[0047] The carbon fibers described above preferably have a surface oxygen concentration ratio [O / C], which is the ratio of the number of oxygen (O) atoms to carbon (C) atoms on the surface of the carbon fibers measured by X-ray photoelectron spectroscopy, of 0.05 or more and 0.5 or less, more preferably 0.08 or more and 0.4 or less, and even more preferably 0.1 or more and 0.3 or less. When the surface oxygen concentration ratio is 0.05 or more, a sufficient amount of functional groups can be secured on the surface of the carbon fibers, thereby further improving adhesion to the matrix resin. When the surface oxygen concentration ratio is 0.5 or less, the carbon fibers are easy to handle and productive. The surface oxygen concentration ratio [O / C] can be measured by the method described in International Publication No. 2017 / 183672. The surface oxygen concentration ratio [O / C] can be controlled by known methods including electrolytic oxidation treatment, chemical oxidation treatment and gas-phase oxidation treatment, but control by electrolytic oxidation treatment is preferred.
[0048] The fiber length (average fiber length) of the reinforcing fibers can be 15 mm or more, preferably 20 mm or more, more preferably 100 mm or more, and even more preferably 500 mm or more. The longer the fiber length of the reinforcing fibers, the higher the bending strength of the fiber-reinforced resin. The upper limit of the fiber length of the reinforcing fibers can be appropriately determined depending on the shape and size of the fiber-reinforced resin, but for example, it can be 50 m or less.
[0049] The average diameter of the reinforcing fibers is preferably between 1 μm and 20 μm, and more preferably between 4 μm and 10 μm. The larger the average diameter of the reinforcing fibers, the higher the bending strength of the fiber-reinforced resin. The smaller the average diameter of the reinforcing fibers, the easier it is to mold the product.
[0050] The reinforcing fibers may be sized with a sizing agent. The sizing agent is not particularly limited, but it preferably contains an unmodified polyolefin and a modified polyolefin, and more preferably contains a modified polyolefin containing a metal carboxylate salt. The modified polyolefin is, for example, obtained by grafting a carboxylic acid group, a carboxylic acid anhydride group, or a carboxylic acid ester group into the polymer chain of an unmodified polyolefin, and forming a salt between the functional group and the metal cation.
[0051] The above unmodified polyolefin is preferably an ethylene-based polymer having a content of 50 mol% or more of constituent units derived from ethylene, or a propylene-based polymer having a content of 50 mol% or more of constituent units derived from propylene. Examples of the above ethylene-based polymer include ethylene homopolymers and copolymers of ethylene and α-olefins having 3 to 10 carbon atoms. Examples of the above propylene-based polymer include propylene homopolymers and copolymers of propylene and ethylene or α-olefins having 4 to 10 carbon atoms. The above unmodified polyolefin is preferably homopolypropylene, homopolyethylene, ethylene-propylene copolymer, propylene-1-butene copolymer, or ethylene-propylene-1-butene copolymer. The monomers constituting these unmodified and modified polyolefins may be derived from component fossil fuels, biomass raw materials, or mixtures thereof.
[0052] The fiber content (fiber volume fraction (Vf)) relative to the total volume of the fiber-reinforced resin is preferably 10% to 70% by volume, more preferably 15% to 60% by volume, and even more preferably 20% to 60% by volume. A higher fiber volume fraction (Vf) increases the bending strength of the fiber-reinforced resin. A lower fiber volume fraction (Vf) makes molding easier.
[0053] The fiber-reinforced resin may be a single-layer UD sheet, or a laminate formed by laminating and fusing multiple UD sheets. It may also be a molded body formed by processing a UD sheet or its laminate into a predetermined shape or fusing it to another component. When the fiber-reinforced resin is a laminate of multiple UD sheets, each layer of the fiber-reinforced resin (each derived from a different UD sheet) may be laminated so that the reinforcing fibers are oriented at the same angle, or it may be laminated so that the reinforcing fibers are oriented at different angles in each layer. From the viewpoint of increasing strength against loads applied from multiple directions, it is preferable that the fiber-reinforced resin has multiple layers in which the reinforcing fibers are oriented at different angles in each layer. In this case, the plurality of layers may include only one or more layers in which the reinforcing fibers are oriented at angles different in only one direction (for example, one or more layers in which the orientation angle is 90° with respect to a reference layer (0°)), or it may include one or more layers in which the reinforcing fibers are oriented at angles different in different directions (for example, one or more layers in which the orientation angles are 45°, 90°, and 135° with respect to a reference layer (0°)). When the fiber-reinforced resin has a plurality of layers in which the reinforcing fibers are oriented at angles different in each layer, it is preferable to set the orientation angles of the reinforcing fibers included in each layer so that the orientation angles of the reinforcing fibers included in the plurality of layers are pseudo-isotropic (that is, when looking at the fiber-reinforced resin as a whole, layers in which the reinforcing fibers are oriented equally in each direction) (for example, 0° / 90° / 0° or 0° / 45° / 90° / 135° / 135° / 90° / 45° / 0°).
[0054] When the material is a laminate of multiple UD sheets, the number of fiber-reinforced resin layers is preferably between 2 and 24, and more preferably between 2 and 18. A smaller number of layers enhances the shapeability of the fiber-reinforced resin, making it easier to form molded articles with a wider variety of shapes. A larger number of layers allows for lamination of reinforcing fiber layers to control strength in specific directions.
[0055] When the material is a laminate of multiple UD sheets, the thickness of the fiber-reinforced resin is preferably 40 μm to 3000 μm, more preferably 100 μm to 2000 μm, even more preferably 300 μm to 1500 μm, and particularly preferably 300 μm to 1200 μm. The greater the thickness of the fiber-reinforced resin, the higher the bending strength of the fiber-reinforced resin. The smaller the thickness of the fiber-reinforced resin, the easier it is to mold.
[0056] The fiber-reinforced resin, which is a single layer of UD sheets or a laminate of multiple UD sheets, may be fused to or fastened to the surface of other articles. Alternatively, the fiber-reinforced resin, which is a laminate of multiple UD sheets, may be a pipe-shaped molded body obtained by sequentially fusing UD sheets around a mandrel and then withdrawing the mandrel. The shape of such a molded body is not particularly limited.
[0057] Furthermore, the fiber-reinforced resin may be a random sheet obtained by randomly scattering chip-shaped UD sheets in a mold, heating, and pressurizing it. The random sheet is a molded article having multiple blocks, each containing multiple reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin.
[0058] [Method for manufacturing fiber-reinforced resin] The fiber-reinforced resin described above can be manufactured by the steps of preparing a composite material comprising a plurality of reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin, and annealing the composite material.
[0059] In the process of preparing composite materials, single-layer UD sheets, laminates thereof, and molded products thereof are prepared. These may be manufactured in this process, or they may be purchased from pre-manufactured sources.
[0060] For example, a composite material that is a single-layer UD sheet can be manufactured by impregnating reinforcing fibers, which are arranged in a unidirectional orientation, with a molten thermoplastic resin composition. The impregnation method is not particularly limited and can be a known method such as roller impregnation, in which the reinforcing fibers are brought into contact (rubbed) with the surface of a rotating roller to which the molten thermoplastic resin composition is attached. The thermoplastic resin composition to be impregnated is a resin composition with the same composition as the matrix resin.
[0061] Furthermore, by stacking the single-layer UD sheets produced in this manner, heating and pressurizing them to fuse the matrix resins together, a composite material consisting of multiple UD sheets can be produced. In this case, the reinforcing fibers of each layer may be varied as described above.
[0062] Furthermore, a single-layer UD sheet or laminated UD sheet produced in this manner can be processed into a predetermined shape, or further, welded or fastened to the surface of other articles to produce a composite material which is a molded UD sheet. The shape of such a molded article is not particularly limited. It is preferable that it does not melt or deform at the heating temperature during annealing. However, this does not apply when other articles are deformed by heating during annealing and simultaneously molded into a desired shape.
[0063] Annealing is performed at the following annealing temperatures, where Tm is the melting point of the matrix resin. Tm -20℃ < Annealing temperature < Tm
[0064] As described above, when attempting to increase the crystallinity of a thermoplastic resin, annealing is usually performed at a temperature near the midpoint between the glass transition temperature (Tg), where the crystallization acceleration is fastest, and the melting point (Tm). In contrast, in this embodiment, annealing is performed at a temperature closer to (higher than) Tm than the aforementioned midpoint, deliberately delaying crystallization. This makes it possible to sufficiently increase the lamellar thickness (increase the long period) and improve the bending properties of the fiber-reinforced resin. From the viewpoint of sufficiently increasing the lamellar thickness, it is preferable to perform annealing at an annealing temperature within the following range. Tm-15℃ < Annealing temperature < Tm-10℃
[0065] When the matrix resin contains multiple types of resins, the melting point of the matrix resin is the melting point of the mixture of these multiple resins. The melting point of the matrix resin can be measured using a differential scanning calorimeter (DSC). When the matrix resin is a mixture of multiple types of resins, the maximum peak measured by the DSC method is taken as the melting point.
[0066] Annealing may be performed on single-layer UD sheets or laminated UD sheets. UD sheets with improved bendability in this way can be used as reinforcing materials by joining them to other articles by fastening, attaching them with adhesives, or melting the surface of the UD sheet and fusing it to other articles. Furthermore, annealing may be performed on molded articles obtained by processing UD sheets or joining them to other articles.
[0067] The above-described method for producing fiber-reinforced resin is not limited to this. For example, when producing a UD sheet, a thermoplastic resin composition containing a crystal nucleating agent with slow crystallization acceleration may be used to form the matrix resin.
[0068] [Other embodiments] The embodiments described above are exemplary embodiments of the present invention, and it goes without saying that the present invention may include embodiments other than those described above within the scope of its core technical concept.
[0069] For example, the method for manufacturing the molded article described above is not limited to those steps only, and may include other steps insofar as the desired molded article is manufactured.
[0070] [Application] The applications of the above-mentioned fiber-reinforced resin molded articles are not limited to primary structural materials including main wings, vertical and horizontal stabilizers, secondary structural materials including ailerons, rudders and elevators, interior materials including seats and tables, components for general aircraft and helicopters including power units, hydraulic cylinders, and composite brakes, rocket components including nozzle cones and motor cases, satellite components including antennas, structures, solar panels, battery cases, and telescopes, mechanical components including frames, shafts, rollers, leaf springs, machine tool heads, robot arms, transport hands, and synthetic fiber pots, high-speed rotating body components including centrifuge rotors and uranium enrichment cylinders, electronic and electrical components including parabolic antennas, battery components, radar, acoustic speaker cones, computer components, printer components, PC casings, and tablet casings, skeletal components, semi-structural components, exterior components, interior and exterior components, power units, other equipment - hydraulic cylinders, brakes, battery cases, drive shafts, engine parts, spoilers, racing car bodies, crash cones, seats, tubs Automotive and motorcycle parts and components including reversals, telephone covers, undercovers, side covers, transmission covers, battery trays, rear steps, spare tire containers, bus and truck body walls, etc.; interior materials, floor panels, ceiling panels, linear motor car bodies, Shinkansen and railway car bodies, window wipers, bogies and seats, etc.; ship hulls including yachts, cruisers and boats, masts, rudders, propellers, rigid sails, screws, military ship hulls, submarine hulls and deep-sea research vessels, etc.; actuators, Pressure vessel components and materials including cylinders, cylinders, hydrogen tanks, CNG tanks and oxygen tanks; scientific equipment components and materials including agitators, pipes, tanks, pit floors and plant piping; wind power generation components and materials including blades, skins, skeletal structures and de-icing systems; X-ray diagnostic equipment components; medical and nursing care equipment components and materials including wheelchairs, artificial bones, prosthetics, crutches, assistive devices and robots (power assist suits), walkers and nursing beds; CF composite cables, concrete reinforcement members, guardrails, bridges, tunnel walls, hoods,It can be used for civil engineering and infrastructure components and materials including cables, tension rods, strand rods, and flexible pipes; offshore oil drilling components and materials including marine risers, flexible jumpers, flexible risers, and drilling risers; sports and leisure goods including fishing rods, reels, golf clubs, tennis rackets, badminton rackets, skis, ski poles, snowboards, ice hockey sticks, snowmobiles, archery equipment, kendo swords, baseball bats, swimming diving boards, sports equipment for people with disabilities, and sports helmets; bicycle parts including frames, disc wheels, rims, handlebars, and saddles; household goods including eyeglasses, bags, umbrellas, and ballpoint pens; and other industrial components and supplies including plastic pallets, containers, logistics materials, resin molds, furniture, umbrellas, helmets, pipes, scaffolding boards, safety shoes, protectors, fuel cell covers, drone blades, frames, jigs, and jig frames. [Examples]
[0071] The present invention will be described in detail based on examples, but the present invention is not limited to these examples.
[0072] 1. Creation of UD sheet 1-1. Preparation of UD Sheet 1 (Example 1) 1-1-1. Reinforced Fibers A carbon fiber bundle (manufactured by Mitsubishi Rayon Co., Ltd., Pyrofil TR50S12L, 24,000 filaments, strand strength 5,000 MPa, strand modulus 242 GPa) was prepared. This carbon fiber bundle was immersed in acetone and subjected to ultrasonic treatment for 10 minutes. After that, the carbon fiber bundle was removed and washed three more times with acetone, and dried at room temperature for 8 hours to remove any adhering sizing agent.
[0073] A mixture obtained by mixing 100 parts by mass of propylene resin (S1), 10 parts by mass of propylene resin (S2), and 3 parts by mass of surfactant was supplied at a rate of 3000 g / hour from the hopper of a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30, L / D=40). Furthermore, a 20% potassium hydroxide aqueous solution was continuously supplied at a rate of 90 g / hour from a supply port provided in the vent section of the extruder, and the mixture was continuously extruded at a heating temperature of 210°C. The extruded resin mixture was cooled to 110°C in a jacketed static mixer installed at the extruder port, and then immersed in 80°C hot water to obtain an emulsion with a solid content of 45%.
[0074] The propylene-based resin (S1) is a propylene-butene copolymer. The propylene-based resin (S1) has a Shore D hardness of 52 and a weight-average molecular weight of 350,000 as measured by GPC.
[0075] Furthermore, the propylene-based resin (S2) was a modified resin obtained by mixing 96 parts by mass of propylene-butene copolymer, 4 parts by mass of maleic anhydride, and 0.4 parts by mass of polymerization initiator (Perhexy 25B, manufactured by Nippon Oil & Fats Co., Ltd.), and modifying it by heating at a temperature of 160°C for 2 hours. The weight-average molecular weight of the propylene-based resin (S2), as measured by GPC, was 20,000, the acid value was 45 mgKOH / g, the maleic anhydride content was 4% by mass, and the melting point was 140°C.
[0076] Furthermore, the surfactant mentioned above is potassium oleate.
[0077] The above emulsion was applied to the carbon fibers using a roller impregnation method. Then, the low-boiling point components were removed by drying online at 130°C for 2 minutes to obtain reinforced fiber bundles with the sizing agent attached. The amount of sizing agent attached to the reinforced fiber bundles was 0.87% by mass.
[0078] 1-1-2. Matrix resin A matrix resin mixture was obtained by melting and kneading 98 parts by mass of propylene resin (P1) and 2.0 parts by mass of propylene resin (P2) at 180°C. The melting point of this matrix resin mixture was measured by DSC method at 163°C, and the MFR measured at 230°C and a 2.16 kg load according to ASTM D1238 was 230 g / 10 min.
[0079] The propylene resin (P1) was unmodified propylene resin (Lyondell basell, Moplen® HP560W, measured according to ASTMD1238 at 230°C with a 2.16 kg load; MFR was 450 g / 10 min and flexural modulus was 1600 MPa).
[0080] Furthermore, the propylene resin (P2) was a modified polypropylene grafted with 0.5% by mass of maleic anhydride (measured according to ASTM D1238, with an MFR of 9.1 g / 10 min and a flexural modulus of over 700 MPa at 230°C and a 2.16 kg load).
[0081] Furthermore, the melting point was measured using the DSC method by sampling 5 mg with a PerkinElmer Diamond DSC and using a PerkinElmer standard pan. Specifically, under a nitrogen atmosphere, the first heating rate was 10°C / min, held at 230°C for 10 minutes, cooled at 10°C / min, held at 30°C for 1 minute, and then heated again at 10°C / min. The peak during the second heating was defined as the melting point.
[0082] 1-1-3. Creating a UD Sheet The opened carbon fiber bundles were aligned and brought into contact with an impregnation roll coated with the molten matrix resin mixture, thereby impregnating the carbon fiber bundles with the matrix resin mixture. The temperature of the molten matrix resin mixture was set to 260°C, and the temperature of the impregnation roll was also set to 260°C.
[0083] The resulting sheet-like composite material contained 66.6% by mass of carbon fibers, and a total of 33.4% by mass of propylene-based resin (P1) and propylene-based resin (P2). The volume-based carbon fiber content (fiber volume fraction: Vf) in the sheet-like composite material was 50% by volume. The thickness of the sheet-like composite material was 150 μm. The MFR of the matrix resin was 230 g / 10 min (measured at 230°C and a 2.16 kg load in accordance with ASTM D1238).
[0084] The resulting sheet-like composite material was placed in an air oven (WFO-410, manufactured by espec) and annealed at 160°C for 1 hour. After that, it was stored in a constant temperature room (23°C, 50RH%) for 72 hours to obtain UD Sheet 1, a fiber-reinforced resin.
[0085] 1-2. Preparation of UD Sheet 2 (Example 2) UD sheet 2 was obtained in the same manner as UD sheet 1, except that the annealing was performed at 150°C for 1 hour.
[0086] 1-3. Preparation of UD Sheet 3 (Comparative Example 1) The sheet-like composite material obtained during the production of UD Sheet 1, before annealing, was designated as UD Sheet 3.
[0087] 1-4. Preparation of UD Sheet 4 (Comparative Example 2) UD sheet 4 was obtained in the same manner as the preparation of UD sheet 1, except that the annealing was performed at 140°C for 1 hour.
[0088] 1-5. Preparation of UD Sheet 5 (Comparative Example 3) UD sheet 5 was obtained in the same manner as the preparation of UD sheet 1, except that the annealing was performed at 140°C for 2 hours.
[0089] 1-6. Preparation of UD Sheet 6 (Example 3) UD sheet 6 was obtained in the same manner as UD sheet 1, except that the amount of matrix resin mixture supplied to the impregnation roll was changed. The volume-based carbon fiber content (fiber volume fraction: Vf) in the sheet-like composite material obtained by impregnation and in UD sheet 6 obtained by subsequent annealing was 38 vol%. The thickness of the sheet-like composite material was 150 μm.
[0090] 1-7. Preparation of UD Sheet 7 (Comparative Example 4) The sheet-like composite material obtained during the production of UD Sheet 6, before annealing, was designated as UD Sheet 7.
[0091] 2. Evaluation The degree of crystallinity and the long period of the lamellae of each UD sheet were measured using the following method.
[0092] (Degree of crystallinity) To determine the degree of crystallinity, WAXD measurements were performed using the transmission method with a NANO-Viewer manufactured by Rigaku Corporation. The measurement conditions were as follows: ·Incoming X-ray: CuKα ray • Detector: X-ray photon counting type 2D detector PILATUS • Distance between sample and detector: 70 mm (for measurement at 23°C), 100 mm (for measurement at 80°C) • Sample thickness: 3mm ·Measurement temperature: room temperature, 80℃
[0093] The scattering intensity I obtained by WAXD measurement is plotted against the magnitude q of the scattering vector defined by equation (1) (where 2θ is the scattering angle and λ is the incident X-ray wavelength), resulting in the scattering intensity curve I(q) [vertical axis is I(q), horizontal axis is q; q is 5 nm]. -1 from 25nm -1 The range of [this range] was separated into peaks using a known analysis program, and the scattering intensity S originating from the crystalline phase was determined. c and scattering intensity S originating from the amorphous phase a Determine the degree of crystallinity φ C This was calculated using equation (2).
[0094] In this case, the broad peak observed around 2θ:11° was designated as Sa, and the peaks observed around 2θ:9.8°, 11.2°, 11.8°, 12.9°, 14.8°, and 15.3° were designated as Sc.
[0095]
number
[0096] (Long period of lamellae) To determine the long period of the lamellae, SAXS measurements were performed using the transmission method with a NANO-Viewer manufactured by Rigaku Corporation. The measurement conditions were as follows: ·Incoming X-ray: CuKα ray • Detector: X-ray photon counting type 2D detector PILATUS • Distance between sample and detector: 1350 mm • Sample thickness: 3mm ·Measurement temperature: 23℃, 80℃
[0097] The long period L is obtained by plotting the scattering intensity I obtained by SAXS measurement against the magnitude q of the scattering vector defined by equation (1) in the scattering intensity curve I(q) [vertical axis is I(q), horizontal axis is q]. 2 The Lorentz-corrected scattering curve obtained by applying the multiplication [vertical axis is q] 2 The peak position qm at ×I(q), where the horizontal axis is q, was determined according to equation (3).
[0098]
number
[0099] 2-2. Bending Test For UD Sheet 1 to UD Sheet 7, the flexural modulus and flexural strength were measured according to the method specified in JIS K7171 (2016), with a test speed of 1 mm / min, a support distance of 48 mm, and test temperatures of room temperature (23°C) and 80°C.
[0100] Tables 1 and 2 show the melting point and MFR of the matrix resin, fiber volume fraction (Vf), annealing temperature and the difference between the melting point and annealing temperature of the matrix resin, as well as the annealing time, crystal long period, degree of crystallinity, and the results of the bending test for UD Sheet 1 to UD Sheet 7. For the bending test results (flexural modulus and flexural strength), the rate of change (increase rate) relative to the unannealed samples (UD Sheet 3 and UD Sheet 7) is also shown.
[0101] [Table 1]
[0102] [Table 2]
[0103] As is clear from Tables 1 and 2, fiber-reinforced resins with a crystal long period of 200 Å or more at 23°C, as determined by small-angle X-ray scattering, showed significantly improved bending properties compared to fiber-reinforced resins with a long period of less than 200 Å. [Industrial applicability]
[0104] The fiber-reinforced resin according to the present invention has high flexural strength. Therefore, the present invention is expected to open up possibilities for the use of fiber-reinforced resins in a wider range of applications, including reinforcing materials, and contribute to the development of various fields related to fiber-reinforced resins.
Claims
1. It comprises a plurality of reinforcing fibers arranged in a unidirectional orientation, and a matrix resin containing a thermoplastic resin. The matrix resin comprises polypropylene, The matrix resin has a crystal long period of 200 Å or more at 23°C, as determined by small-angle X-ray scattering. Fiber-reinforced resin.
2. The matrix resin has a degree of crystallinity of 45% or more at 80°C. The fiber-reinforced resin according to claim 1.
3. The aforementioned polypropylene has a melting point of 163°C or lower. The fiber-reinforced resin according to claim 1.
4. The aforementioned polypropylene has a melt flow rate (MFR) of 100 mm / 10 min or more, measured at 230°C and a 2.16 kg load, in accordance with ASTM D1238. The fiber-reinforced resin according to claim 1.
5. The reinforcing fiber includes carbon fiber, The fiber-reinforced resin according to claim 1.
6. The fiber volume fraction (Vf) is between 20% and 60%. The fiber-reinforced resin according to claim 1.
7. A step of preparing a composite material comprising a plurality of reinforcing fibers arranged in a unidirectional orientation and a matrix resin containing a thermoplastic resin, The composite material is annealed at an annealing temperature within the following range, where Tm is the melting point of the matrix resin. Tm -20°C < Annealing temperature < Tm It has, The matrix resin includes polypropylene. A method for manufacturing fiber-reinforced resin.
Citation Information
Patent Citations
Polypropylene composition
JP1995018151A
Long-fiber reinforced polyamide resin molded product
JP2013253215A
Composite material for thermoforming
JP2017043672A
